2004
DOI: 10.1161/01.cir.0000141728.23033.b5
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Atorvastatin Reduces Total Plasma Levels of Oxidized Phospholipids and Immune Complexes Present on Apolipoprotein B-100 in Patients With Acute Coronary Syndromes in the MIRACL Trial

Abstract: Background— Oxidized phospholipids (OxPL) are present within atherosclerotic plaques and bound by lipoprotein (a) [Lp(a)] in plasma. This study evaluated the impact of atorvastatin on oxidized LDL (OxLDL) in patients with acute coronary syndromes (ACS). Methods and Results— OxLDL-E06 (OxPL content on apolipoprotein B-100 [apoB] detected by antibody E06), apoB-100 immune complexes (apoB-IC), OxLDL autoantibodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
153
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(170 citation statements)
references
References 52 publications
14
153
0
3
Order By: Relevance
“…Interestingly, reductions in oxidation markers were observed at its lowest dose (10 mg) over just 12 weeks (15). In a larger study of 2341 patients, treatment with a high dose of atorvastatin (80 mg) caused a significant reduction in levels of oxidized lipids on all apoB-100 particles after just a 16-week period (14). Comparative studies into the effects of atorvastatin versus other statins on biomarkers of oxidative stress are currently underway and will provide additional insight into this potential non-LDL mechanism of action.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, reductions in oxidation markers were observed at its lowest dose (10 mg) over just 12 weeks (15). In a larger study of 2341 patients, treatment with a high dose of atorvastatin (80 mg) caused a significant reduction in levels of oxidized lipids on all apoB-100 particles after just a 16-week period (14). Comparative studies into the effects of atorvastatin versus other statins on biomarkers of oxidative stress are currently underway and will provide additional insight into this potential non-LDL mechanism of action.…”
Section: Discussionmentioning
confidence: 95%
“…Unlike other statins, ATM has the same enzymatic activity as its parent. Atorvastatin treatment has been successfully used to reduce the risk and progression of cardiovascular disease (16 -18), but there is also clinical evidence that this agent has anti-inflammatory and antioxidant properties that may not be solely related to LDL reduction (12)(13)(14)(15). A small clinical study that measured protein oxidation markers (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only practical approach at this time is to reduce the antigenic load, either by dietary modification, or by pharmacological means. Statins have been shown to reduce the levels of circulating modified LDL-IC in two studies [97,98], and have also anti-inflammatory and antioxidant effects [99][100][101]. Their effects on modified LDL-IC levels should be investigated in a well designed trial with sufficient numbers of patients and methodological rigor, designed to determine how much of the benefits attributed to statins can be correlated with the reduction of the major pro-inflammatory insult that mLDL-IC appear to represent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also found that atorvastatin modestly decreased the Lp (a) levels (17). However, other studies didn't find the statins' beneficial effects on the Lp (a) reductions (18)(19)(20). We think that it's reasonable the statins exhibit beneficial effects in reducing the Lp (a) levels given that the statins can deplete apolipoprotein B100 (apo B), which is indispensable to assemble the Lp (a).…”
Section: Introductionmentioning
confidence: 99%